Recomposição do ecossistema florestal da nascente do rio Uraim localizado no município de Paragominas/PA. - SANTOS, Emilene Moreira (2019)
The work looked to recompose and protect 05 hectares of areas of permanent preservation of the River Uraim, located in the municipality of Paragominas, in the State of Pará. The study was conducted in the area of coverage of one of the springs, which is a 42.2km from the urban area of the municipality between coordinates 047 ° 24'07 .3 W and 03 ° 16'09 .1 S. The methodology proposed adopted as a strategy to identify the study area, the raising history of the area, the characterization of the site, the characterization of the vegetation cover, the recomposition of the area - which had 03 phases (cleaning, operating procedures and evaluation of the mortality and growth up of seedlings planted), the involvement of society, and guidance to the owner of the area. As a result, this study showed that the area has a small vegetable cover, attributed to the fact that no forest remnants in their spill and to be more distant fragment of forest existing in the proximity of the area. It also justifies the intensive cultivation of grasslands in the proximity of the springs, without considering the legislation. With the participation of many social actors and production and planting of 3.000 seedlings of native species, it was found that there was a recovery of 1.520 species, mainly from Tachigali myrmecophila, with a growth of 300%, Macrolobium sp with 180%, with 200 Ingá edules and Euterpe oleraceae, with increase of 150%, the others suffered by caused by grass braquiarão (Brachiaria brisantha). The action of recovery made possible the formation of new values front to environmental issues. It can be said that sustainable development was started, but there is still a long way to be covered and new actions should be directed to achieving the proper planning and management of river basins.